2008
DOI: 10.1002/pssb.200879577
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent photoluminescence study of ErSc2N@C80 and Er2ScN@C80 fullerenes

Abstract: The photoluminescence study of the Er3+ ion in ErSc2N@C80 and Er2ScN@C80 fullerenes in the temperature range of 5 K to 80 K is presented. New emission peaks are observed for both fullerenes above 20 K. These peaks arise from thermally populated crystal‐field levels of the excited state. An anomalous behaviour of the PL peak area is observed with an increasing temperature which reveals an internal rearrangement of the cluster ErSc2N in ErSc2N@C80. (© 2008 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…It is known that the ground state of Er 3+ ion ( 4 I 15/2 ) consists of eight doublet sublevels . The most intensive emission peak centered at around 1520 nm corresponds to the transition of 4 I 13/2 (1) → 4 I 15/2 (1), and the adjacent peak centered at 1540–1550 nm corresponds to the transition of 4 I 13/2 (1) → 4 I 15/2 (3) . Some weak bands at 1480–1500 nm are observed at low temperature.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It is known that the ground state of Er 3+ ion ( 4 I 15/2 ) consists of eight doublet sublevels . The most intensive emission peak centered at around 1520 nm corresponds to the transition of 4 I 13/2 (1) → 4 I 15/2 (1), and the adjacent peak centered at 1540–1550 nm corresponds to the transition of 4 I 13/2 (1) → 4 I 15/2 (3) . Some weak bands at 1480–1500 nm are observed at low temperature.…”
Section: Resultsmentioning
confidence: 96%
“…Endohedral metallofullerenes are core–shell structured complexes with a metal core encapsulated in the hollow interior of a fullerene cage. , The encapsulation of rare-earth metal atoms in fullerenes has received considerable interest from the scientific community , since rare-earth elements are widely used in optical and magnetic materials. An array of interesting optical and magnetic properties of rare-earth endohedral fullerenes have been disclosed, such as their single-molecule magnetism, enhanced nonlinear optical response, and photoluminescence properties. The fluorescence from erbium-, thulium-, thorium-, and uranium-based metallofullerenes have been reported previously. ,, Nevertheless, fluorescence activities of other lanthanide atoms inside fullerene cages have not been observed so far, which is a result of the significant quenching effect of the fullerene cage.…”
Section: Introductionmentioning
confidence: 99%
“…Photoluminescence (PL) has previously been reported from the Er 3+ ion in ErSc 2 N@C 80 around 1.5 µm [3,9,10], revealing that the ErSc 2 N cluster inside the C 80 cage occupies two dominant spatial configurations, corroborating earlier X-ray crystallographic studies [11]. At low temperatures, one of the configurations is favoured over the other, and illumination with visible light was found to switch the ErSc 2 N molecular cluster inside the cage from one configuration to the other [12].…”
Section: Introductionmentioning
confidence: 99%
“…The situation can be changed if endohedral metal atoms have low-energy emitting states, and near-infrared lanthanide-based luminescence had been observed in Er-and Tm-based EMFs. 19,[43][44][45][46][47][48] Surprisingly, Y 3 N@C 80 was found to show unusually strong luminescence and long uorescence lifetimes, but the reasons for this unexpected behaviour rst remained unclear. 49,50 Recently we found that the strong photoemission of Y 3 N@C 80 is caused by the small singlet-triplet S 1 -T 1 gap of less than 0.1 eV, which enables thermally activated delayed uorescence (TADF) via thermal population of the emitting S 1 state from the T 1 "reservoir".…”
Section: Introductionmentioning
confidence: 99%